Biology of the greenbug in different hosts - Cruz, Ivan; Vendramim, José Djair (Pesquisa Agropecuaria Brasileira, 2014)
The experiments were conducted during 1983 to 1985 in Sete Lagoas, MG, Brazil, at the National Corn and Sorghum Research Center (CNPMS) of EMBRAPA. The hosts were a susceptible sorghum ('BR 601'), corn (C-111'), soybean ('Doko'), rice (Irga 409) and wheat ('Allondra'). The insects were reared on excised leaves, under laboratory conditions and on whole plants in the greenhouse. In both cases the artificial infestation was made when the plants were eleven days old. The temperature and relative humidity were measured by a thermohygrograph. The photophase for laboratory experiments was twelve hours and for greenhouse experiments was 14 ± 2 hours. It was concluded that corn and soybean were not suitable to the insect development. The rice, in spite of causing high nymphal mortality, under some conditions, can be an alternative host to the greenbug. The wheal although worse than the sorghum was, as expected, an adequated host to the insect Schizaphis graminum (Rondani, 1852).